A novel research reactor concept based on coated particle fuel. (March 2015) - Hidayatullah, Rully; Hartanto, Donny; Kim, Yonghee
Highlights: A plate fuel based on coated particle fuel (CPF) for research reactors was studied. Characteristics of the CPF-based core were compared to conventional reactors. The Doppler effect can be significantly enhanced due to higher fuel temperature. A very high thermal flux on the order of 10 14 neutrons/cm 2 sec can be achieved. Abstract: This work presents a preliminary study of a novel plate-type fuel concept for a high-performance and ultra-safe research reactor. This new fuel type consists of coated particle fuel (CPF) randomly dispersed in an aluminum matrix with a certain packing fraction that can be adjusted depending on the reactor design requirements. The CPF can also be varied in the fuel kernel material between UC and UO2 . For the purpose of this study, UO2 was used as the reference fuel type. Using this novel fuel type, a 20 MWth pool-type research reactor was investigated to determine the preliminary performance and safety characteristics of the new fuel. The core thermal analysis was done using the MATRA-P code. The neutronics analysis was done using the Monte Carlo Serpent code for an equilibrium cycle resulting from a multi-batch fuel management. In this analysis, it was found that the Doppler effect is significantly enhanced through the implementation of CPF, in turn improving the inherent safety of the reactor. In addition to the notable improvement in safety, the new fuel type also promises to be able to achieve a high thermal neutron flux, improving the performance and utility of the reactor. It is concluded that the CPF-based fuel concept presented in this paper can enable new high-flux reactor designs using simple plate-type fuels with improved safety.